Fear of falling: A manifestation of executive dysfunction? - Kenny, Rose; Kennelly, Sean; Feeney, Joanne (My University, 2019)
Objective: Fear of falling (FoF) may be an early marker of decline in global cognitive functioning, but associations with specific domains of cognitive functioning are unclear. The aim was to examine associations between FoF and 4-year decline in memory, processing speed, and executive functioning in adults aged 50 years and older. Methods: Data were from 5174 participants (mean age = 62.6 ± 8.9 years, range = 50-91, 54.5% female) in The Irish Longitudinal Study on Ageing, a population-based study. Measurements: FoF was self-reported in 2009 to 2011. Immediate and delayed recall, Colour Trails 1 and 2, choice reaction time, sustained attention to response task, and verbal fluency were measured in 2009 to 2011 and 2014 to 2015. Prospective associations between FoF and domains of cognitive functioning were examined using linear mixed modelling. Adjustment was made for demographic and health factors. Interactions with age were examined. Results: In 2009 to 2011, 20.6% of participants reported FoF. No statistically significant interaction of FoF with age was found for any of the associations (P ≥ .06). Participants with FoF had greater decline on delayed recall (B = -0.19; 95% CI, -0.32 to -0.06), verbal fluency (B = -0.52; 95% CI, -0.88 to -0.18); and the ln-transformed scores for the Colour Trails 1 test (B = -0.04; 95% CI, -0.07 to -0.01) and the Colour Trails 2 test (B = -0.04; 95% CI, -0.06 to -0.02) than participants without FoF. No statistically significant associations were found for any of the other outcomes. Conclusions: FoF may be an indicator of decline in domains of cognitive functioning, particularly those related to executive function and processing speed. However, studies with longer follow-up and/or higher average age are required to confirm this.
PUBLISHED
Keywords: anxiety, cognitive function, executive function, old age; Ageing